Analisis Kualitas Air pada Jalur Distribusi Air Bersih di Gedung Baru Fakultas Ekonomi dan Manajemen Institut Pertanian Bogor - Daeng Barang, Millah Hudiyah; Saptomo, Satyanto Krido (Jurnal Teknik Sipil dan Lingkungan, 2019)
One of the causes of the decreasing of water quality was the increasing of inappropriate human activities that caused water pollution. Cihideung River was being made as water resource in the campus area which the water have been used for a lot of activities in IPB Dramaga Campus. The purpose of this research were to analyze the clean water quality from the ground water tank (GWT) in Cihideung to the new buildings of the FEM, to compare the result with a national quality standard, to determine the criteria of clean water quality based on STORET method, and to analyze the influence of time and weather to the water quality. The parameters which had concentration below the standard were TDS, turbidity, temperature, iron, fluoride, chloride, manganese, and sulfate, and biological parameters like the total coliform/E.coli. The parameters which exceeded the standard were the value of color of 60 TCU in Cihideung GWT at rainy afternoon and pH of 6.38 in wing 1 sanitary at rainy morning. According to the US-EPA system, the water quality of distribution channels of FEM new building were classified into grade B, that meant light contaminated.Key words: distribution channels, quality standard, water pollution, water quality